Peran Perpustakaan Dalam Mengurangi Plagiarisme - Ilham Mashuri (Pustakaloka, 2013)
Abstract: Plagiarism is a problem that happened long time not only in Indonesia, but also abroad. Although this country had copy right law (UU No. 19 Tahun 2002), but the number of plagiarism is still high. Library as a information resources has important role to decrease the number of plagiarism. Steps can be done by library are socializing the rules of plagiarism, upload the academic work, providing online database for submitting assignment, practicing information literacy, and cooperating with educators.